2017
DOI: 10.1186/s12974-017-0818-5
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cell frequency, but not plasma IL-33 levels, represents potential immunological biomarker to predict clinical response to intravenous immunoglobulin therapy

Abstract: BackgroundIntravenous immunoglobulin (IVIG) is a polyspecific pooled immunoglobulin G preparation and one of the commonly used therapeutics for autoimmune diseases including those of neurological origin. A recent report in murine model proposed that IVIG expands regulatory T (Treg) cells via induction of interleukin 33 (IL-33). However, translational insight on these observations is lacking.MethodsTen newly diagnosed Guillain-Barré syndrome (GBS) patients were treated with IVIG at the rate of 0.4 g/kg for thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 43 publications
1
12
2
Order By: Relevance
“…A recent report that looked at cytokine/chemokine induction by IVIg, using a multiplex cytokine assay and two different strains of mice with ITP that respond to IVIg, has shown that IL-33 is produced following IVIg treatment only in BALB/cJ mice, but not in C57BL/6J mice [41]. This supports other studies which have shown that IL-33 is not involved in the mechanism of IVIg action [42]. However, high amounts of IL-4 were produced in both mouse strains upon IVIg induction.…”
Section: Introductionsupporting
confidence: 76%
“…A recent report that looked at cytokine/chemokine induction by IVIg, using a multiplex cytokine assay and two different strains of mice with ITP that respond to IVIg, has shown that IL-33 is produced following IVIg treatment only in BALB/cJ mice, but not in C57BL/6J mice [41]. This supports other studies which have shown that IL-33 is not involved in the mechanism of IVIg action [42]. However, high amounts of IL-4 were produced in both mouse strains upon IVIg induction.…”
Section: Introductionsupporting
confidence: 76%
“…In addition to IL-33, which is mainly produced by epithelial and endothelial cells, IL-3 secreted by activated T cells and mast cells is also known for inducing priming of basophils. 17,[33][34][35][36] We sought to confirm whether human basophil priming by IL-33 at a dose equivalent to that induced by IVIG in patients with rheumatic and neurologic autoimmune diseases 11,12 would stimulate IL-4 production, as proposed from mouse studies. IL-33 primed human basophils (based on CD69 expression) and induced IL-4, 37 but the extent of priming was only marginal when compared with IL-3mediated priming.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike IL-3 (Fig 1, D-F), only a marginal increase in expression of CD69 on basophils (Fig 2, A and B) or their cytokine production (Fig 2, C) was observed after IL-33 stimulation of basophils at a dose equivalent of that induced in IVIG-treated patients. 11,12 Despite enhancement of IL-33R expression by IL-3 (see Fig E4 in this article's Online Repository at www.jacionline.org), IL-33 when used in combination with IL-3 did not exert either a synergistic or additive effect on IVIG-induced basophil activation (Fig 2, D and E). Hence these results do not support a major role for IL-33 in priming human basophils toward IVIG responsiveness.…”
Section: Il-33 and Other Cytokines Are Dispensable For Basophil Activmentioning
confidence: 96%
“…However, translation of these findings to humans failed to recapitulate the mechanisms although requirement of sialylation has been confirmed in other experimental models [78,79,82,83,88,89,92]. Studies in humans have revealed that IVIG can directly interact with basophils to induce IL-4 secretion, and can act either directly on Tregs or on DCs to expand Tregs [46,65,[93][94][95][96].…”
Section: Natural Igg (Nigg): Role Of Nabs In Immune Tolerance/homeostmentioning
confidence: 99%